2020
DOI: 10.3390/agronomy10020314
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Recycling, Wheat Straw Decomposition, and the Potential Effect of Straw Shear Strength on Soil Mechanical Properties

Abstract: This study aimed to explore the release rate (RR) of wheat straw nutrients during straw return to a paddy field and examined the possible relationship between wheat stalk shear strength and the content of the remaining components in wheat straw. We used the nylon mesh bag technique to study the decomposition of straw nutrients such as total organic carbon (TOC), total nitrogen (TN), total phosphorus (TP), total potassium (TK), lignin, and cellulose over time. During the time span of 0–90 days, results showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…This result implies that the release rate was, on average, always higher for P than for N. This was previously observed in pea under no-till farming [43]. Wang et al [29] indicated that P and K in straw are released during short-term straw return, while C and N are released during long-term straw return. In our case, only K was clearly released in the short term.…”
Section: C N and P Modellingsupporting
confidence: 67%
See 1 more Smart Citation
“…This result implies that the release rate was, on average, always higher for P than for N. This was previously observed in pea under no-till farming [43]. Wang et al [29] indicated that P and K in straw are released during short-term straw return, while C and N are released during long-term straw return. In our case, only K was clearly released in the short term.…”
Section: C N and P Modellingsupporting
confidence: 67%
“…There is very scarce information on the nutrient release from aboveground residues during the decomposition of CCs in olive groves. Research on nutrient release has usually been performed in arable crops with no-till systems [28,29]. Some works have considered only the living stage of CCs [30].…”
Section: Introductionmentioning
confidence: 99%
“…While most studies have focused on litter decomposition in forests [5][6][7], less attention has been paid to this ecological process in agricultural lands. In agroecosystems, large quantities of straw are generated as byproducts from several crops, such as wheat and other cereals, and aid in maintaining soil organic matter content and supplying nutrients to subsequent crops [8].…”
Section: Introductionmentioning
confidence: 99%
“…Once the straw is returned to the soil, some nutrients are easily converted into CO2 by the mineralization of microorganisms in the soil. Wang et al (2020) have revealed that wheat straw components and nutrients are rapidly released in the natural environment under different tillage practiceswithout additives such as biomass and organic fertilizers-between 0 and 90 days. However, lignin remaining in the straw, cellulose and straw organic carbon in the hemicellulose remain in the soil longer because macromolecules such as lignin cannot be easily assimilated and converted by bacteria in the soil (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%